Níveis de suprimento de energia via suplemento para desempenho de bovinos de corte em pastagem tropical - Stahlhoferh, Mariane (2017)
This study aimed to evaluate the effect of energy levels supplying by means of supplement on the productive performance and nutritional characteristics of beef cattle in tropical pastures. Twenty-eight young Nellore bulls were used, with average initial body weight of 325.2 ± 4.1 kg, randomly divided into four groups of 7 animals each. The bulky food relied solely on pasture comprising Urochloa brizantha cv. Xaraes. The evaluated treatments were T0 – without supplementation, T15 – 15% of the requirement of TDN supplied by the supplement, T30 – 30% of the requirement of TDN supplied by the supplement and T45 – 45% of the requirement of TDN supplied by the supplement. The animals of all treatments received mixed mineral supplements ad libitum. The experiment lasted 84 days divided into 3 subperiods of 28 days. Total dry matter intake was not influenced by treatments, however, there has been a decreasing linear effect on dry matter intake of pasture and neutral detergent fiber intake. The dry matter intake of supplements, organic matter intake, non-fibrous carbohydrate intake, intake of digestible organic matter and intake of ether extract presented increasing linear effect in function of TDN in the supplement. Crude protein intake showed quadratic effect to increased levels of TDN of the supplement. The apparent digestibility coefficients of dry matter, non-fibrous carbohydrates and ether extract presented increasing linear effect. The apparent digestibility coefficient of crude protein, neutral detergent fiber and organic matter presented quadratic effect to TDN supplement levels. The average daily gain presented linear plateau effect with establishment of plateau with average daily gain of 1.276 kg at 16.40% TDN supply by supplement. Grazing behavior variables presented linear effect descending to the hours of grazing and growing to no grazing. There was significant effect between the animals not supplemented and supplemented in the thickness of subcutaneous fat cover and on the difference between the final and initial subcutaneous fat, however, the thickness of subcutaneous fat showed no significant difference between animals supplemented. The concentration of serum urea nitrogen and nitrogen in the urine showed treatment effect, and collection period interaction between treatment and period of collection. Already the concentration of ammoniacal nitrogen in the rumen showed no interaction between treatment and period. The energy supply by supplement up to the 16.40% level of TDN animals requirement raises the performance of beef cattle in tropical grasslands of high quality. However, those gains are reflected in high forage replacement